â€œLaper Kuprerâ€ dalam Pembelajaran Pendidikan Agama Islam Kompetensi Alquran - Futihatun Futihatun (Jurnal Edutrained : Jurnal Pendidikan dan Pelatihan, 2023)
This research is descriptive qualitative research, with the aim of understanding the process of teaching and learning activities in Al-Quran competencies in Islamic Religious and Character Education, as well as efforts to activate students by learning using teaching aids, in the form of posters. This research uses observational research, focus groups, and document analysis. Learning uses teaching aids. The material contained in the teaching aids is discussed through group discussions and presented using gadget technology to record and share the recordings on familiar social media, known to students. This learning is termed "Laper Kuprer" (Props, Discussion, Presentation, Recording). The results of the research show that the process of teaching and learning activities for Al-Quran competencies in Islamic Religious and Character Education at SMK Negeri 1 Depok with "Laper Kuprer" is very effective in increasing student activity. Based on the research results, the author recommends that in learning use "Laper Kuprer" to implement differentiated learning, increasing students' enthusiasm, participation and creativity by using devices that are familiar and interesting to them.